Prevalence of burnout among nurses at the Nephrology Center-Benghazi - Eltarhuni Ainas; Akram Alabdali; Eman Alaqeli; Salma Omar Imhamed (Aljameai, 1970)
Abstract:   Burnout is a growing problem in the workplace worldwide, particularly in healthcare settings among healthcare professionals. Thus, this study was aimed at determining the prevalence of burnout among nursing staff working in the Nephrology Center and identifying the difference and relationship between burnout degree subscales according to general nurses. The descriptive statistics (frequency and percentage) have been used to determine the levels of job burnout. The sign test or t-test was used to find out the respondents’ attitudes, and the chi-square test was used to find out the existence of a relationship between general characteristics. Result: The results of this study revealed a high prevalence of burnout and emotional exhaustion and a moderate prevalence of depersonalization, while personal accomplishment was low. There was a significant association between total burnout, gender, and marital status. Regarding the dimensions of burnout, emotional exhaustion was significantly associated with gender and education. Depersonalization was insignificantly associated with nurses' general data. Personal accomplishment was significantly associated with a nurse's experience.Conclusion: This study has concluded that there is a high prevalence of burnout syndrome among nurses. Administrative support and improving the workplace environment to reduce burnout were recommended for more attention by policymakers.المستخلص:   يؤدي الاحتراق الوظيفي في مكان العمل إلى تدني الأداء الوظيفي، مما يعني انخفاض كفاءة العاملين في المجالات المختلفة، لا سيما في المجال الصحي، وخصوصا العاملين بمهنة التمريض ، وبالتالي تهدف هذه الدراسة إلي  تحديد مدى انتشار ظاهرة الاحتراق الوظيفي بين طاقم التمريض العاملين بمركز أمراض الكلى بمدينة بنغازي وكذلك التعرف على وجود فروق معنوية حسب محاور مقياس ماسلاك ( الاجهاد الانفعالي ، وتبلد المشاعر ، الانجاز الشخصي )، فضلاً عن ذلك التعرف على علاقة بعض الخصائص الشخصية للمبحوثين بمحاور الدراسة. ولقد استخدمت التكرارات والنسب المئوية للتعرف على مدى انتشار الاحتراق الوظيفي بين المبحوثين، وأظهرت النتائج إن ثلثي عينة الدراسة تقريبا يعانون من احتراق وطيفي مرتفع، وباقي عينة الدراسة يعانون من احتراق وظيفي متوسط، وتم استخدم اختبار الإشارة أو ما يعرف باختبار (t) لعينة واحدة، بغية التعرف على مدي وجود فروق معنوية في المتوسطات. وأظهرت النتائج وجود هكذا فروق معنوية لمحاور الدراسة، وتشير قيم الوسط الحسابي التي تزيد عن قيمة الوسط الفرضي للبعد الأول والثاني على وجود احتراق وظيفي ، بينما تشير قيمة الوسط الحسابي للمحور الثالث والتي تقل عن الوسط الفرضي إلى وجود احتراق وظيفي ( محور عكسي ). ومن جانب آخر تُظهر نتائج الدراسة وجود علاقة ذات دلالة معنوية بين كلاً من الجنس والحالة الاجتماعية ودرجة الاحتراق الوظيفي بأبعاده الثلاثة، فـي حـين يتضح من أبعاد الاحتراق الاتي: الاجهاد الانفعالي له دلالة معنوية مع الجنس ومستوى التعليم. وتقدم الدراسة توصية لمتخذي القرارات المعنيين بشأن ضرورة توفير بيئة عمل مناسبة للممرضين بهدف تقليل ظاهرة الاحتراق الوظيفي، والذي يمكن ان يتحقق من خلال تحسين ظروف بيئة العمل وتقديم الدعم المادي والمعنوي وبذل الجهود للتعلم والاستفادة من تجارب الدول السابقة في مجال الدعم النفسي للعاملين بمجال التمريض.